Immersive experience and customer responses towards mobile augmented reality applications: The moderating role of technology anxiety - Kim Nhan Vo; Angelina Nhat Hanh Le; Le Thanh Tam; Huong Ho Xuan (Cogent Business & Management, 2022)
The purpose of this study is to investigate the impact of customer immersive experience on attitude and adoption intention toward mobile augmented reality applications (MAR apps). This paper also examines the moderating role of technology anxiety on the relationship between immersive experience on attitude and adoption intention toward MAR apps. A dataset of 322 customers and the partial least square structural equation model (PLS-SEM) with the SmartPLS 3.2.8 statistical software were used to test the proposed hypotheses. The results show that immersive experience significantly affects attitude and adoption intention toward MAR apps. In addition, the vital role of technology anxiety in moderating the relationship between customer immersive experience and their responses toward MAR apps is revealed.
Keywords: 650; adoption intention; attitude; customer immersive experience; mobile augmented reality applications; technology anxiety